EPID-14. RACIAL DIFFERENCES AND DISPARITIES IN PATIENTS WITH GLIOMAS: A SINGLE COMPREHENSIVE CANCER CENTER EXPERIENCE FROM 2008–2020. (9th November 2020) - Coffee, Elizabeth; Tucker, Zachary; Lobbous, Mina; Baskin, Monica; Markert, James; Fiveash, John; Miller, C Ryan; Nabors, Louis
Abstract: BACKGROUND: Disparities in healthcare delivery in the United States based on race and socioeconomic status are well-documented. Our study examined these disparities along with demographic differences in patients with gliomas. METHODS: Data was collected retrospectively from an NCI Comprehensive Cancer Center between 2008–2020; 163 African-American patients and 1207 non-Hispanic white patients were included. Demographic variables were entered as predictors of tumor grade and type in an ANOVA model and multinomial logistic regression, respectively. A MANOVA model was used to assess differences in treatments received. Predictors of outcome were determined using cox regression. RESULTS: Significant differences (p< 0.05) were found between African-American and non-Hispanic white patient groups in; age at diagnosis (48.68 vs 56.12 years, respectively), male/female gender ratio (0.75 vs 1.22), annual household income ($29, 442 vs $40, 028), insurance type (53.1% private and 42% public vs 63.4% private and 33.6% public) and marital status (43% married vs 74.1%). When controlling for these, there were no significant differences in tumor grade, type, MGMT methylation or IDH1 alteration statuses. Race alone did not predict treatment received, however, two-way interactions between race and other variables did. While gender differences in resection were small for non-Hispanic white controls, resection took place more often in African-American females than males (F = 4.779, p = 0.029). The deleterious effect of increased age on overall survival was diminished in African-Americans (B = -0.033, p < 0.001), while the effect of tumor grade was more pronounced (B = 0.595, p < 0.001). DISCUSSION: This study suggests that disparities in outcomes are identified when race is considered within the context of other demographic, socioeconomic, and clinical factors. Moreover, these observations demonstrate the need for further studies into intersectional effects on treatment access and clinical outcomes, along with aggressive countermeasures to ensure equity of care.